2022
DOI: 10.1186/s13041-022-00929-4
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous expression of an allatotropin-related peptide receptor increased the membrane excitability in Aplysia neurons

Abstract: Neuropeptides act mostly on a class of G-protein coupled receptors, and play a fundamental role in the functions of neural circuits underlying behaviors. However, physiological functions of some neuropeptide receptors are poorly understood. Here, we used the molluscan model system Aplysia and microinjected the exogenous neuropeptide receptor apATRPR (Aplysia allatotropin-related peptide receptor) with an expression vector (pNEX3) into Aplysia neurons that did not express the receptor endogenously. Physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…To determine the selectivity of ALKs on the ALKR, we tested the effects of ALK1 on a different Aplysia receptor ( 9 , 59 ), that is, the receptor for Aplysia allatotropin-like peptide ( 45 ). ALK1 did not show any activation of Aplysia allatotropin-like peptide receptor ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the selectivity of ALKs on the ALKR, we tested the effects of ALK1 on a different Aplysia receptor ( 9 , 59 ), that is, the receptor for Aplysia allatotropin-like peptide ( 45 ). ALK1 did not show any activation of Aplysia allatotropin-like peptide receptor ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, few have explored the contributions of specific residues or other properties of ligands to receptor activity based on the structure of a protostome’s receptor that has no known homologs in deuterostomes (vertebrates and some invertebrates), partly because a protein structure cannot be obtained using a homology modeling approach. In the present work, we utilize a molluscan model system, Aplysia californica ( 11 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ), to study this issue using Aplysia leucokinin peptides (ALKs) ( 60 ) and their receptor. In particular, recent successful efforts ( 14 ) have been made to predict protein structure based on the amino acid sequence of a protein, particularly template-free modeling ( 61 ) using artificial intelligence (AI) deep machine learning algorithms such as Robetta ( 62 ) and AlphaFold ( 63 ).…”
mentioning
confidence: 99%
“…Neuropeptides are the most diverse class of neuromodulators that act on G-protein coupled receptors (GPCRs) to regulate a variety of motivated behaviors ( Nassel and Zandawala, 2019 ; Taghert and Nitabach, 2012 ; Cropper et al, 2018a ; Abid et al, 2021 ; Nusbaum et al, 2017 ; Zhang et al, 2022 ). Among them, vasopressin (VP) and oxytocin (OT) signaling systems are of significant interest ( Carter et al, 2020 ) because they have been shown to play a variety of roles in olfaction ( Gravati et al, 2010 ; Tobin et al, 2010 ; Knobloch et al, 2012 ), social interactions ( Arakawa et al, 2010 ; Choleris et al, 2007 ; Griffin and Flanagan-Cato, 2011 ), metabolism ( Altirriba et al, 2014 ; Deblon et al, 2011 ; Le et al, 2011 ; Mohan et al, 2018 ), fear conditioning ( Huber et al, 2005 ; Wilson et al, 2005 ; Cenquizca and Swanson, 2007 ), learning ( Bielsky et al, 2005 ; Veenema et al, 2010 ; Curley et al, 2012 ), and sensory and motor regulation ( Breton et al, 2008 ; Schorscher-Petcu et al, 2010 ; Wagenaar et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…We sought to study an oxytocin/vasopressin signaling system in the gastropod mollusc Aplysia californica . Aplysia is an experimentally-advantageous system and has provided fundamental insight into the neural basis of motivated behaviors ( Jing and Weiss, 2002 ; Jing et al, 2004 ; Sasaki et al, 2009 ; Jing et al, 2010 ; Sasaki et al, 2013 ; Zhang et al, 2020 ; Bedecarrats et al, 2021 ; Evans et al, 2021 ; Due et al, 2022 ; Wang et al, 2023 ), learning and memory ( Sieling et al, 2014 ; Byrne and Hawkins, 2015 ; Orvis et al, 2022 ) and neuromodulation ( Cropper et al, 2018b ; Zhang et al, 2022 ), including neuropeptides ( Livnat et al, 2016 ; Zhang et al, 2017 ; Do et al, 2018 ; Zhang et al, 2018 ; Chan-Andersen et al, 2022 ) and receptors ( Bauknecht and Jekely, 2015 ; Checco et al, 2018 ; Guo et al, 2022 ; Jiang et al, 2022 ; Zhang et al, 2022 ). The first evidence for the presence of oxytocin/vasopressin-related neuropeptide in protostomes comes from an early immunohistochemical study ( Remy et al, 1979 ), and the later identification of an arginine vasopressin-like diuretic hormone ( Proux et al, 1987 ), both in insects.…”
Section: Introductionmentioning
confidence: 99%
“…In the current work, we sought to characterize two Wamide neuropeptide signaling systems: GWa and MIP families, in a model system, mollusk Aplysia californica . Aplysia has emerged in recent years as a powerful lophotrochozoan/spiralians laboratory animal for the study of neuronal circuits, motivated behaviors, , and neuromodulation. , …”
Section: Introductionmentioning
confidence: 99%